2013
DOI: 10.1093/nar/gkt548
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary conserved pattern of 18S rRNA sequence complementarity to mRNA 5′ UTRs and its implications for eukaryotic gene translation regulation

Abstract: There are several key mechanisms regulating eukaryotic gene expression at the level of protein synthesis. Interestingly, the least explored mechanisms of translational control are those that involve the translating ribosome per se, mediated for example via predicted interactions between the ribosomal RNAs (rRNAs) and mRNAs. Here, we took advantage of robustly growing large-scale data sets of mRNA sequences for numerous organisms, solved ribosomal structures and computational power to computationally explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…5E). Since the predominant material within the ribosome is rRNA (rRNA) and 18S rRNA is a critical component of the 40S subunit that facilitates binding to the 5′ untranslated region of mRNA, 29 we next verified the results of A254 absorbance by measuring 18S rRNA content by RT-PCR. Similar to A254 absorbance identical amount of 18S rRNA was evident in B6 wt and B6 SLy1− NK cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…5E). Since the predominant material within the ribosome is rRNA (rRNA) and 18S rRNA is a critical component of the 40S subunit that facilitates binding to the 5′ untranslated region of mRNA, 29 we next verified the results of A254 absorbance by measuring 18S rRNA content by RT-PCR. Similar to A254 absorbance identical amount of 18S rRNA was evident in B6 wt and B6 SLy1− NK cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…A recent bioinformatic study demonstrated an evolutionary conserved pattern of complementarity between 18S rRNA and mRNA 5 -UTRs [59], providing weight to the argument that such interactions could be biologically significant. Furthermore, the rRNA regions showing significant complementarity to 5 -UTRs were found to be clustered within the evolutionarily recent expansion segments of 18S rRNA, which are exposed on the surface of the ribosome.…”
Section: Does Eif4a Have a Role In Unwinding Mrna-rrna Duplexes?mentioning
confidence: 99%
“…This would also provide a gratifying evolutionary hypothesis to explain the role of the expansion regions for translational regulation. Panek et al [59] hypothesize that interactions between mRNA exiting the scanning 40S ribosome form hybrid structures with complementary sequences in the 18S rRNA expansion regions and that these 'sticky elements' could impede scanning during translation initiation. eIF4A activity could therefore be required to unwind these duplexes during scanning and we feel this certainly deserves further investigation.…”
Section: Does Eif4a Have a Role In Unwinding Mrna-rrna Duplexes?mentioning
confidence: 99%
“…Conserved sequences indicate potential functions and/or play important roles in cell development and regulation [137][138][139]. As a rule, coding region sequences are highly conserved.…”
Section: Conservation Analysismentioning
confidence: 99%